Utilization of AI in Optimizing Supervision of Handling of General Criminal Acts by Law Enforcement Officers - Sirot, Sirot; Santiago, Faisal (CV. Syntax Corporation Indonesia, 2025)
This research explores the utilization of Artificial Intelligence (AI) in optimizing the supervision of law enforcement officers handling general criminal cases. The study is motivated by the need to enhance efficiency and reduce procedural errors within the criminal justice system. The primary objective is to evaluate the effectiveness of AI-based supervision in improving key performance metrics. A simulated quantitative research design was employed using a pre-test/post-test control group approach. Two hypothetical groups of 50 officers each were observed: an experimental group receiving AI-based supervision and a control group under traditional supervision. Data were collected before and after the intervention to assess performance changes. The results showed that AI-based supervision significantly reduced procedural errors, shortened case processing time, and increased case completion rates compared to traditional methods. Independent samples t-tests confirmed the statistical significance of these improvements (p < 0.001). The study concludes that AI has strong potential to enhance supervisory effectiveness and operational efficiency in law enforcement.